2023
DOI: 10.3389/fpubh.2023.1137191
|View full text |Cite
|
Sign up to set email alerts
|

A positive association between the prevalence of circadian syndrome and overactive bladder in United States adults

Abstract: ObjectiveTo explore the association between the prevalence of circadian syndrome (CircS) and overactive bladder (OAB).Materials and methodsCross-section analysis was based on the National Health and Nutrition Examination Survey 2005–2018. Data regarding OAB was collected from questionnaires. The association between the prevalence of CircS and OAB was elucidated using three multivariable logistic regression models. Stratified and interaction analyses were performed to find whether some factors can modify the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The incidence of AEs related to mirabegron were higher in females (60.10%) than in males (34.80%), excluding cases with unknown gender. This may be related to the higher prevalence of OAB in females compared to males ( Xiao et al, 2023 ). Furthermore, with age increases, the prevalence of OAB increased gradually ( Song et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AEs related to mirabegron were higher in females (60.10%) than in males (34.80%), excluding cases with unknown gender. This may be related to the higher prevalence of OAB in females compared to males ( Xiao et al, 2023 ). Furthermore, with age increases, the prevalence of OAB increased gradually ( Song et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…After collecting the results, the researchers employed the Overactive Bladder Symptom Score (OABSS) to determine the severity of OAB [ 18 ]. Participants scoring 3 or more were grouped as having OAB [ 19 21 ]. All details are outlined in Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported associations between CircS and unhealthy dietary patterns, stroke, kidney stones, overactive bladder, and testosterone deficiency [ 18 , 19 , 20 , 21 , 22 ]. CircS also appears to have a mediating effect in the relationship between air pollution and CVD [ 23 ].…”
Section: Introductionmentioning
confidence: 99%